Gambaran Penerapan Program Kesehatan Dan Keselamatan Kerja Serta Faktor Yang Mempengaruhi Pada Perawat Di RSIJ Sukapura Jakarta Utara - Desya Nanda Sri Wahyuni; Siti Rukayah (STIKes Persada Husada Indonesia, 2018)
The hospitals become one of the places that must apply the Occupational Safety and Health Management System (SMK3).The purpose of this study is to find out the description of the application of Health and Safety Program Hospital and the factors causing the nurses at RSIJ Sukapura Year 2018.This study uses a qualitative method. Data were collected through in-depth interviews, direct observation and document review. The results of this study examine about personal protective equipment, signs and safety signs, causes of accidents, examination MCU, and periodic checks in RSIJ Sukapura North Jakarta on the implementation of K3 is on the road right.MCU checks and periodic checks have been carried out and are mandatory programs from hospitals to employees, especially nurses.The implementation of OSH is carried out in the form of training, socialization, provision of personal protective equipment, and health checks. The RSIJ Sukapura party is expected to implement a more stringent Standard Operating Procedure (SPO), and improve supervision of officers' compliance in using PPE.